ANALISIS PEMBERIAN HADIAH DALAM PRODUK SIMPANAN BERJANGKA WADIAH (SAJADAH) DI BMT NU CABANG MLANDINGAN SITUBONDO - Bayu Aria Pratama; Faizatul Ummah (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2024)
Baitul Mal wat Tamwil (BMT) is one form of sharia-based Microfinance Institution (MFI). The name BMT has two terms, namely the term baitul maal which means the management of worship treasures and the term baitul tamwil which means the collection and distribution of commercial funds. In BMT there are several financing products like other financial institutions, as well as the NU BMT in the Situbondo area which has several financing products. However, there is one product that is interesting to study at BMT NU Mlandingan Situbondo Branch, namely the wadiah prize savings product (SAJADAH) where customers will get a gift directly when opening the savings but with an agreed period of time. This is interesting to be used as research material because in a wadiah contract it is not allowed to promise a gift at the beginning of the contract. In this research, normative research is used while the approach used is an analytical approach where the SAJADAH savings product is the object of research. The results obtained from the analysis of gift giving in the wadiah contract that occurs at BMT NU Mlandingan Situbondo Branch are that this practice is permissible because the practice of giving gifts at BMT NU Situbondo is in accordance with the provisions of the DSN-MUI fatwa and the purpose of giving these gifts does not violate the provisions of the Sharia